اثر استخدام نظرية Dubinsky في تحصيل مادة الرياضيات لدى طلاب الصف الاول المتوسط. (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of Dubinsky's theory on the achievement of mathematics among first-year middle school students. The research sample amounted to (60) students from first-year middle school. Al-Nabugh Intermediate School for Boys, affiliated with the Directorate of Education in Babylon, Al-Mahawil District, was randomly selected. The school contains four sections (A, B, C, D) .The two sections (B, D) were randomly selected to represent the experimental sample, as section (B) represente the experimental group and section (D) represented the control group. The two groups were rewarded with variables (intelligence, previous knowledge in mathematics, previous achievement in mathematics, chronological.age calculated in months,previous achievement of parents). The experiment was applied in the second semester of the academic year (2024 – 2025).An achievement test was prepared that included two questions. The first question included (20) objective multiple-choice items, while the second question included (5) essay items. The reliability coefficient was extracted using the (Cronbach's alpha) equation, where its value reached (0.857), and after collecting data and using appropriate statistical methods for the research, the results showed the superiority of the experimental group who studied using Dubinsky's theory over the control group who studied using the traditional method in the achievement test. In light of the results obtained, the researcheقrecommended training teachers and instructors on how to use Dubinsky's theory to apply its steps in teaching mathematics, and to work on developing mathematics books in line with the steps of Dubinsky's theory.